Tribological Behavior of Doped DLC Coatings in the Presence of Ionic Liquid Additive under Different Lubrication Regimes - Sadeghi, Mohammadamin (2023)
Diamond-like carbon (DLC) coatings are widely used in industries that require high durability and wear resistance, and low friction. The unique characteristics of DLC coatings allow for the possibility of creating adsorption sites for lubricant additives through the doping process. In this study, the combined use of europium-doped diamond-like carbon (Eu-DLC), gadolinium-doped diamond-like carbon (Gd-DLC), and pure DLC coatings and an ionic liquid (IL) additive, namely, trihexyltetradecylphosphonium bis (2-ethylhexyl) phosphate [P66614] [DEHP], with a 1 wt.% concentration in polyalphaolefin (PAO) 8 as a base lubricant was investigated. Higher hardness, higher thin-film adhesion, a higher ratio of hardness to elastic modulus, and a higher plastic deformation resistance factor were achieved with the Gd-DLC coating. The CoF of the Gd-DLC coating paired with the IL was superior compared to the other pairs in all lubrication regimes, and the pure DLC coating had a better performance than the Eu-DLC coating. The wear could not be quantified due to the low wear on the surface of the DLC coatings. The friction reduction demonstrates that tribological systems combining Gd-DLC thin films with an IL can be a potential candidate for future research and development efforts to reduce friction and increase the efficiency of moving parts in internal combustion engines, for instance.